Influencia del soporte familiar en el tratamiento de los pacientes esquizofrénicos atendidos en el Centro de Salud Mental Comunitario El Porvenir, 2021 - Benites Nima, Estefany Nicoll (2022)
The present research was carried out with the purpose of analyzing the influence of family support in the treatment of schizophrenic patients treated at the El Porvenir Community Mental Health Center. The sample consisted of 20 schizophrenic patients, in which the development of the research methods such as deductive, inductive, statistical and analytical-synthetic were applied, as well as techniques such as the interview and the survey that were presented through the interview guide instruments, interview record and the survey questionnaire, which were applied to the patients together with their families, arrived at qualitative and quantitative data allowing the analytical understanding of the indicators and their variables. According to the analysis carried out and the results obtained in the research, it is evident that family support influences the treatment of schizophrenic patients by 45% in relation to communication, 60% in relation to care, 45% in relation to attention and 50% in relation to the family union that occurs in the family home; taking into account that 75% of the patients have generated positive changes since they began their treatment due to adequate monitoring and care.